2017
DOI: 10.1177/1941874417704753
|View full text |Cite
|
Sign up to set email alerts
|

The Door to Needle Time Metric Can Be Achieved via Telestroke

Abstract: The administration of intravenous (IV) alteplase to patients with stroke via telestroke (TS) can be safe and effective. It remains unclear how quickly IV alteplase occurs during TS evaluations. We sought to compare door to needle times (DNTs) between patients receiving IV alteplase who present directly to our comprehensive stroke center (CSC) and those presenting to community hospitals in our TS network. Consecutive patients with acute ischemic stroke (AIS) who presented to emergency departments and received I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
(8 reference statements)
0
7
1
Order By: Relevance
“…This is supported by a retrospective analysis by Blech et al 12 which found a 31‐minute reduction in DNT with tele‐stroke implementation, with the significant intervention effect compared to Nguyen‐Huynh et al 92 likely due to variations in pre‐intervention workflow efficiency. This contrasts with the findings from Asaithambi et al 88 , which found DNT delays of 11 minutes with the use of tele‐stroke care, with results likely skewed by sampling bias and efficient pre‐intervention workflows. Although tele‐stroke care has been championed as a solution to effectively disseminate neurology expertise in regional/remote areas, further prospective studies are required to substantiate the workflow, therapeutic effects and safety of tele‐stroke care and its components over longer time periods.…”
Section: In‐hospital Workflow Parameterscontrasting
confidence: 94%
See 2 more Smart Citations
“…This is supported by a retrospective analysis by Blech et al 12 which found a 31‐minute reduction in DNT with tele‐stroke implementation, with the significant intervention effect compared to Nguyen‐Huynh et al 92 likely due to variations in pre‐intervention workflow efficiency. This contrasts with the findings from Asaithambi et al 88 , which found DNT delays of 11 minutes with the use of tele‐stroke care, with results likely skewed by sampling bias and efficient pre‐intervention workflows. Although tele‐stroke care has been championed as a solution to effectively disseminate neurology expertise in regional/remote areas, further prospective studies are required to substantiate the workflow, therapeutic effects and safety of tele‐stroke care and its components over longer time periods.…”
Section: In‐hospital Workflow Parameterscontrasting
confidence: 94%
“…First proposed in 1999, there is a growing body of evidence supporting its use, efficacy and potential to expedite acute stroke reperfusion treatment delivery. 12,88,89 Tele-stroke may be used in triaging patients for EVT. 20,21 Current AHA guidelines support the use of tele-stroke care when on-site expertise is unavailable, with two meta-analyses confirming no difference in mortality or functional outcomes with the implementation of a tele-stroke clinical decision-making system.…”
Section: Tele-stroke Carementioning
confidence: 99%
See 1 more Smart Citation
“…Many spoke sites had made tremendous improvements in their DTN times. 13,27,28 In many cases, the DTN processes may have little room for further efficiencies. Across the examined care processes of DIDO time, transportation time, and TSC door to puncture time, DIDO accounted for the longest time frame.…”
Section: Discussionmentioning
confidence: 99%
“…Our TS practice ensures that stroke expertise is available in the acute setting during all hours of the day, which results in a higher proportion of patients receiving IV alteplase 60 minutes of arrival to the hospital when compared to other TS practices. 13 A similar study was performed evaluating the effects of weekend and after-hour presentation on the acute treatment of ischemic stroke; however, generalizability is limited as the study was performed in an academic setting where trainees were involved in the care of patients studied. 14 Our study has important limitations.…”
Section: Discussionmentioning
confidence: 99%